Negative electrode sheet, secondary battery, and electric device
Patent Information
- Application Number
- CN202511366113.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-23
- Publication Date
- 2026-10-20
AI Technical Summary
[0005](1)上下层石墨动力学差异较大影响锂离子传输;
[0019]负极材料层的多个子材料层将第一石墨和第二石墨掺混,并限定第一石墨和第二石墨在距离集流体最远的子材料层中的质量比(R1)高于它们在距离集流体最近的子材料层中的质量比(RN),可降低极片厚度方向上由于动力学和孔隙率差异突然变化导致的锂离子浓差极化(也即浓度梯度差),进而降低析锂风险,提升快充性能和使用寿命。
Smart Images

Figure BDA0005611375890000171 
Figure BDA0005611375890000181 
Figure BDA0005611375890000231
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, and in particular to a negative electrode sheet, a secondary battery, and an electrical device. Background Technology
[0002] With the rapid development of new energy vehicles, higher requirements have been placed on battery charging speed and lifespan.
[0003] Fast-charging systems offer better kinetic performance in terms of negative electrode graphite and electrolyte, but increased side reactions and active lithium consumption during cycling and storage lead to slower capacity decay compared to non-fast-charging systems, impacting battery lifespan and vehicle resale value. Long-life batteries utilize low-expansion, low-lithium-consumption graphite, but their kinetic performance is poor and does not meet fast-charging requirements.
[0004] To balance charging speed and battery life, related technologies employ composite electrode designs based on an upper layer of high-kinetic-performance fast-charging graphite (i.e., the first graphite, 0.3365nm ≤ interlayer spacing ≤ 0.3385nm) and a lower layer of lower-kinetic-performance long-life graphite (i.e., the second graphite, 0.3355nm ≤ interlayer spacing < 0.3365nm). Figure 1 (as shown), but the inventors discovered at least the following drawbacks:
[0005] (1) The significant difference in kinetics between the upper and lower graphite layers affects lithium-ion transport;
[0006] (2) Different types of graphite have large differences in tap density. After rolling, there are significant differences in porosity between the upper and lower electrode layers. When charging at high rate, the concentration polarization at the interface between the upper and lower layers increases, which causes the risk of lithium plating during fast charging and cycle decay, resulting in deterioration of charging speed and service life.
[0007] (3) The combination of two types of graphite in the upper and lower layers makes it impossible to accurately adjust the charging speed and lifespan of the battery cell, which affects product performance and increases verification time and cost.
[0008] Therefore, there is an urgent need for a negative electrode plate that can overcome at least one of the above defects. Summary of the Invention
[0009] This application aims to at least partially address one of the technical problems in the related art.
[0010] Therefore, one objective of this application is to provide a negative electrode sheet in which multiple sub-material layers of the negative electrode material layer are mixed with first graphite and second graphite, and the mass ratio of first graphite and second graphite in the sub-material layer farthest from the current collector is higher than their mass ratio in the sub-material layer closest to the current collector. This can reduce lithium-ion concentration polarization (i.e., concentration gradient difference) caused by sudden changes in kinetics and porosity differences in the thickness direction of the electrode sheet, thereby reducing the risk of lithium plating and improving fast charging performance and service life.
[0011] Another objective of this application is to provide a secondary battery.
[0012] Another object of this application is to provide an electrical device.
[0013] To achieve the above objectives, the first aspect of this application provides a negative electrode sheet, comprising:
[0014] current collector;
[0015] A negative electrode material layer is disposed on at least a portion of at least one surface of the current collector. The negative electrode material layer comprises N sub-material layers stacked along a direction close to the surface of the current collector, where N ≥ 2. The sub-material layers comprise a first graphite and a second graphite, wherein the interlayer spacing of the first graphite is a nm and the interlayer spacing of the second graphite is b nm, and a and b satisfy: 0.3365 ≤ a ≤ 0.3385, 0.3355 ≤ b < 0.3365.
[0016] Define R as the mass ratio of the first graphite to the second graphite in the i-th submaterial layer along the direction close to the surface of the current collector. i If 1 ≦ i ≦ N, then the negative electrode material layer satisfies:
[0017] R1>R N .
[0018] The negative electrode sheet described in this application can bring at least the following beneficial effects:
[0019] The negative electrode material layer comprises multiple sub-material layers in which first graphite and second graphite are mixed, and the mass ratio (R1) of first graphite and second graphite in the sub-material layer farthest from the current collector is defined as higher than their mass ratio (R2) in the sub-material layer closest to the current collector. N This can reduce lithium-ion concentration polarization (i.e., concentration gradient difference) caused by sudden changes in kinetics and porosity differences in the thickness direction of the electrode, thereby reducing the risk of lithium plating and improving fast charging performance and service life.
[0020] In some embodiments, the negative electrode material layer also has at least one of the following characteristics:
[0021] a) When N≧3, R N ≦R i+1 ≦R1, where 2≦i+1≦N-1;
[0022] b) 0 < R N ≤3;
[0023] c) 1≦R1≦6;
[0024] d)R1 to R N Gradual decrease, gradient decrease, or step decrease are all possible options, with gradient decrease or step decrease being the preferred choice.
[0025] In some implementations, N satisfies: 2≦N≦8.
[0026] In some embodiments, the negative electrode material layer further includes a negative electrode binder, and the mass content of the negative electrode binder in the i-th sub-material layer along the direction close to the surface of the current collector is defined as P. i %, then the negative electrode material layer satisfies:
[0027] P1 < P N .
[0028] In some embodiments, the negative electrode material layer has at least one of the following characteristics:
[0029] e) When N ≥ 3, P1 ≦ P i+1 ≦P N Where 2≦i+1≦N-1;
[0030] f)2≦P N ≤4;
[0031] g)0<P1≦2.5;
[0032] h)P1 to P N Gradual increase, gradient increase, or step-like increase are all possible options, with gradient increase being the preferred choice.
[0033] i) In each of the sub-material layers, the first graphite, the second graphite, and the negative electrode binder are all uniformly distributed;
[0034] j) The negative electrode binder includes at least one of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), styrene-acrylic emulsion, and carboxymethyl cellulose (CMC).
[0035] In some implementations, when N is 2, the negative electrode material layer satisfies:
[0036] 1≦R1≦4, can be 7 / 3≦R1≦4; and / or, 1.5≦P1≦2.5, and / or, 0<R2≦1, can be 1 / 4≦R2≦3 / 7; and / or, 2≦P2≦3.
[0037] In some implementations, when N is 3, the negative electrode material layer satisfies:
[0038] 7 / 3≦R1≦4, and / or, 1.5≦P1≦2.5, and / or, 3 / 7≦R2≦7 / 3, and / or, 1.8≦P2≦2.8, and / or, 0<R3≦3 / 7, and / or, 2.1≦P3≦3.1.
[0039] In some implementations, when N is 4, the negative electrode material layer satisfies:
[0040] 4≦R1≦6, and / or, 1.5≦P1≦2.1, and / or, 3 / 2≦R2≦4, and / or, 1.7≦P2≦2.3, and / or, 1 / 4≦R3≦3 / 2, and / or, 1.9≦P3≦2.5, and / or, 0<R4≦1 / 4, and / or, 2.2≦P4≦4.
[0041] In some embodiments, the raw materials for preparing the first graphite include at least one of petroleum low-sulfur coke or needle coke.
[0042] In some embodiments, the sulfur content in the low-sulfur petroleum coke is less than 1 wt%.
[0043] In some embodiments, the raw materials for preparing the second graphite include at least one of petroleum sulfur coke or needle coke.
[0044] In some embodiments, the sulfur content in the petroleum sulfur coke is 1-5 wt%.
[0045] In some embodiments, the first graphite has at least one of the following characteristics:
[0046] (1) The particle size of Dv50 is 9-16μm;
[0047] (2) The particle size of Dv99 is below 65μm;
[0048] (3) The specific surface area of BET is 0.95-1.45㎡ / g.
[0049] In some embodiments, the second graphite has at least one of the following characteristics:
[0050] (1) The particle size of Dv50 is 11-18 μm;
[0051] (2) The particle size of Dv99 is below 80 μm;
[0052] (3) The specific surface area of BET is 0.8-1.3㎡ / g.
[0053] In some embodiments, the Dv50 particle size of the second graphite is larger than that of the first graphite.
[0054] In some embodiments, the Dv99 particle size of the second graphite is larger than that of the first graphite.
[0055] In some embodiments, the specific surface area of the second graphite is smaller than that of the first graphite.
[0056] In some embodiments, the current collector includes at least one of copper foil, carbon-coated copper foil, etc.
[0057] A second aspect of this application provides a secondary battery, comprising a positive electrode, a negative electrode, and a separator, wherein the negative electrode is the negative electrode described in this application.
[0058] In some embodiments, the positive electrode includes a positive electrode material, and the positive electrode material includes a positive electrode lithium supplement.
[0059] The secondary battery described in this application can bring at least the following beneficial effects:
[0060] 1. Introducing a positive electrode lithium replenishment scheme provides additional active lithium to compensate for the active lithium consumed during cycling and storage, thus extending the lifespan. Simultaneously, the volume shrinkage of the lithium replenishment material during the first charge (formation) process increases the porosity of the positive electrode, and the oxygen release reacts with the electrolyte to increase the proportion of inorganic components in the negative electrode SEI film, reducing lithium-ion transport impedance and improving kinetic performance.
[0061] 2. Negative Electrode Design – In the multiple sub-material layers of the negative electrode material layer, the first graphite and the second graphite are mixed, and the mass ratio (R1) of the first graphite and the second graphite in the sub-material layer farthest from the current collector is limited to being higher than their mass ratio (R2) in the sub-material layer closest to the current collector. N (For example, gradient design) Compared to related technologies that use different types of graphite in the upper and lower layers (the upper layer being the one furthest from the current collector and the lower layer being the one closest to the current collector), this approach can reduce lithium-ion concentration polarization caused by sudden changes in kinetics and porosity differences along the thickness direction, improving fast-charging performance and reducing the risk of lithium plating. Simultaneously, controlling the content of the sub-material layer furthest from the current collector to be lower than that in the sub-material layer closest to the current collector (e.g., gradient design) can reduce ion transport impedance, improving the problem of kinetic degradation on the side furthest from the current collector due to the floating of the negative electrode binder near the current collector during high-speed mass production coating, and reducing the risk of insufficient adhesion on the side closest to the negative electrode and current collector.
[0062] In some embodiments, the positive electrode lithium supplement includes at least one of lithium-rich lithium iron ore (LFO) and lithium-rich lithium nickel ore (LNO).
[0063] In some embodiments, the positive electrode lithium supplement has a mass content of 0.5-5% in the positive electrode material.
[0064] In some embodiments, the cathode material further includes a cathode active material, which includes at least one of lithium iron phosphate and ternary materials, wherein the ternary material includes a ternary cathode material containing nickel, cobalt and manganese.
[0065] In some embodiments, when the positive electrode active material is lithium iron phosphate, the upper limit voltage of the secondary battery is below 3.8V, and / or the positive electrode lithium replenishing agent is lithium iron phosphate and lithium nickel phosphate, and the mass ratio of lithium iron phosphate to lithium nickel phosphate is c, 1≤c≤5.
[0066] In some embodiments, when the positive electrode active material is the ternary material, the upper limit voltage of the secondary battery is 4.2-4.5V, and / or the positive electrode lithium replenishing agent is the lithium iron ferrite and the lithium nickel ferrite, and the mass ratio of the lithium iron ferrite and the lithium nickel ferrite is d, 0 < d ≤ 1.
[0067] A third aspect of this application provides an electrical device comprising the secondary battery described in this application.
[0068] In some embodiments, the electrical device includes a vehicle.
[0069] The electrical device described in this application has at least the beneficial effects of the negative electrode plate and the secondary battery described in this application.
[0070] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0071] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the following description of the embodiments taken in conjunction with the accompanying drawings.
[0072] in:
[0073] Figure 1 This is a schematic diagram of the structure and principle of a composite electrode (e.g., Comparative Example 1) in the related technology.
[0074] Figure 2 This is a schematic diagram and principle illustration of a negative electrode sheet (e.g., Example 1) shown in an exemplary embodiment of this application, wherein the x-direction represents the direction of this application along the surface of the current collector.
[0075] Figure 3This is a schematic diagram of the structure of a negative electrode sheet, which is shown as another exemplary embodiment of this application.
[0076] Figure 4 This is a schematic diagram of the structure of a negative electrode sheet, which is another exemplary embodiment of this application.
[0077] Figure label:
[0078] 100 - Current collector; 200 - Negative electrode material layer; 201 - First sub-material layer; 202 - Second sub-material layer; 203 - Third sub-material layer. Detailed Implementation
[0079] The embodiments of this application are described in detail below, with examples of these embodiments illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain this application, and should not be construed as limiting this application.
[0080] In this application, the disclosure of numerical ranges includes all values throughout the range and the disclosure of further subdivisions of the range, including the endpoints and subranges given for these ranges.
[0081] Unless otherwise specified, all raw materials and equipment involved in this application are self-made through commercial means or known methods; and all methods involved are conventional methods unless otherwise specified.
[0082] When the term “and / or” is used in a list containing two or more items, it means that any of the listed items can be used alone or in combination with any one or more of the listed items. For example, the expression “A and / or B” is intended to mean A or B or A and B, that is, A only, B only, or a combination of A and B.
[0083] In this application, Dv50 refers to the particle size corresponding to 50% of the volume distribution.
[0084] In this application, Dv99 refers to the particle size corresponding to 99% of the volume distribution.
[0085] <Negative electrode sheet>
[0086] Figure 2 This is a schematic diagram of the structure and principle of the negative electrode sheet shown in an exemplary embodiment of this application.
[0087] like Figure 1 As shown, the negative electrode sheet in this embodiment includes a current collector and a negative electrode material layer.
[0088] The negative electrode material layer is disposed on at least a portion of at least one surface of the current collector, and the negative electrode material layer comprises N sub-material layers stacked along a direction close to the surface of the current collector, where N ≧ 2; the sub-material layers comprise a first graphite and a second graphite, the interlayer spacing of the first graphite being a nm and the interlayer spacing of the second graphite being b nm, wherein a and b satisfy: 0.3365 ≤ a ≤ 0.3385, 0.3355 ≤ b < 0.3365;
[0089] Define R as the mass ratio of the first graphite to the second graphite in the i-th submaterial layer along the direction close to the surface of the current collector. i If 1 ≦ i ≦ N, then the negative electrode material layer satisfies:
[0090] R1>R N .
[0091] Understandably, R1 > R N The mass ratio of the first graphite and the second graphite in the sub-material layer furthest from the current collector is defined to be greater than the mass ratio of the first graphite and the second graphite in the sub-material layer closest to the current collector.
[0092] The negative electrode sheet of this application embodiment can bring at least the following beneficial effects:
[0093] The negative electrode material layer comprises multiple sub-material layers in which first graphite and second graphite are mixed, and the mass ratio (R1) of first graphite and second graphite in the sub-material layer farthest from the current collector is defined as higher than their mass ratio (R2) in the sub-material layer closest to the current collector. N This can reduce lithium-ion concentration polarization (i.e., concentration gradient difference) caused by sudden changes in kinetics and porosity differences in the thickness direction of the electrode, thereby reducing the risk of lithium plating and improving fast charging performance and service life.
[0094] It should be emphasized that, in the embodiments of this application, if R1 < R N If the above-mentioned beneficial effects cannot be achieved, the possible reason is that the proportion of the first graphite in the sub-material layer farthest from the current collector is insufficient, which will cause the rapid transport channel of lithium ions inside the electrode to be blocked, and polarization is likely to occur during charging. The proportion of the second graphite in the sub-material layer closest to the current collector is relatively reduced, and its stabilizing effect on the electrode structure is weakened. After multiple charge and discharge cycles, the electrode material of the sub-material layer closest to the current collector is prone to accelerated capacity decay due to structural damage, and the cycle life is greatly shortened.
[0095] It is understandable that the negative electrode material layer can be disposed on one surface of the current collector or on multiple surfaces of the current collector; at the same time, for the surface of the current collector with the negative electrode material layer, the negative electrode material layer can be disposed in all or part of the surface.
[0096] As an alternative example, the negative electrode material layer is arranged parallel to the length direction of the current collector. In this case, the direction closest to the surface of the current collector is... Figure 2 The x-direction in the middle.
[0097] In some embodiments, the current collector is a negative current collector.
[0098] It should be noted that in the embodiments of this application, there are no restrictions on the material and specifications of the negative electrode current collector. It can be any negative electrode current collector known in the art that can be used for negative electrode sheets of secondary batteries, especially lithium-ion batteries, such as copper foil, carbon-coated copper foil, etc.
[0099] In some embodiments, in the submaterial layer between the submaterial layer furthest from the current collector and the submaterial layer closest to the current collector, the mass ratio (R) of the first graphite to the second graphite is... i (i is not 1 and N) may be greater than R1 and R N However, this method may have the following drawbacks: the lithium-ion diffusion rate in this region is much faster than that in the sub-material layer furthest from the current collector. When lithium ions migrate from the current collector to the inside of the electrode, a transport bottleneck will form in the sub-material layer furthest from the current collector due to insufficient first graphite, while the rapid diffusion in the middle region will cause a large accumulation of lithium ions, which can easily lead to the growth of local lithium dendrites and pose a safety hazard of battery short circuit.
[0100] In other embodiments, the negative electrode material layer also has at least one of the following characteristics:
[0101] a) When N≧3, R N ≦R i+1 ≦R1, where 2≦i+1≦N-1;
[0102] b) 0 < R N ≤3;
[0103] c) 1≦R1≦6;
[0104] d)R1 to R N Gradual decrease, gradient decrease, or step decrease are all possible options, with gradient decrease or step decrease being the preferred choice.
[0105] The above a) defines that, except for the sub-material layer furthest from the current collector and the sub-material layer closest to the current collector, the mass ratio of the first graphite to the second graphite in the remaining sub-material layers can be equal to, equal to, or between the mass ratio of the sub-material layer furthest from the current collector and the sub-material layer closest to the current collector. In this case, along the direction close to the surface of the current collector, R1 to R... N The trend of change can be a gradual decrease, a gradient decrease, or a step-like decrease, as shown in d), with gradient decrease or step-like decrease being the preferred options. This setting can better reduce the lithium-ion concentration gradient difference along the electrode thickness direction, reduce the risk of lithium plating, and improve fast charging performance and lifespan.
[0106] It should be noted that, in the embodiments of this application, "gradual reduction" refers to the mass ratio of the first graphite and the second graphite decreasing continuously in a linear or nonlinear manner along the direction close to the surface of the current collector (for example, the mass ratio of the first graphite and the second graphite in each sub-material layer gradually decreases along the direction close to the surface of the current collector, and the mass ratio of the first graphite and the second graphite in all sub-material layers also continuously and gradually decreases along the direction close to the surface of the current collector); "gradient reduction" refers to the situation where the mass ratio of the first graphite and the second graphite in each sub-material layer remains constant along the direction close to the surface of the current collector, but the mass ratio of the first graphite and the second graphite in all sub-material layers decreases layer by layer along the direction close to the surface of the current collector). "Stepwise reduction" refers to the mass ratio of the first graphite and the second graphite decreasing in a discontinuous manner along the direction close to the surface of the current collector (for example, the mass ratio of the first graphite and the second graphite in each sub-material layer is equal in some layers along the direction close to the surface of the current collector, but all are at R... N (Below and above R1).
[0107] The aforementioned gradual reduction method is relatively difficult to implement in practice for preparing the negative electrode sheet, but it may have the best effect in reducing the lithium-ion concentration gradient difference along the electrode thickness direction, thereby reducing the risk of lithium plating, improving fast charging performance, and extending service life. Gradient reduction and step reduction are relatively easier to implement in practice for preparing the negative electrode sheet, with gradient reduction showing the second best effect, and step reduction showing the least effect. Therefore, considering the ease of preparation, along the direction close to the current collector surface, R1 to R... N The changing trend can be either gradient decrease or stepwise decrease.
[0108] The above c) 0 < R N ≦3 defines the range of the mass ratio of the first graphite to the second graphite in the submaterial layer closest to the current collector. R N Within the aforementioned range, both battery cycle stability and interfacial reactivity can be balanced. For example, R...N The values can include, but are not limited to, 0.5, 1, 1.5, 2, 2.5 or 3.
[0109] The above d)1≦R1≦6 defines the range of the mass ratio of the first graphite and the second graphite in the sub-material layer furthest from the current collector. Within this range, R1 can achieve an efficient balance between fast-charging performance and structural stability. For example, the values of R1 include, but are not limited to, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, or 6.
[0110] In some embodiments, the total mass content of the first graphite and the second graphite in the sub-material layer is 94-98%, including but not limited to 94%, 95%, 96%, 97%, or 98%. When the total mass of the first graphite and the second graphite in the sub-material layer is within the aforementioned range, their synergistic effect can be fully utilized, while ensuring the overall performance of the negative electrode material layer.
[0111] In some embodiments, the submaterial layer further includes a negative electrode binder.
[0112] In some embodiments, the mass content of the negative electrode binder in the i-th sub-material layer along the direction close to the surface of the current collector is defined as P. i %, then the negative electrode material layer satisfies:
[0113] P1 < P N .
[0114] It is understandable that P1 < P N The mass content of the negative electrode binder in the sub-material layer furthest from the current collector is limited to less than the mass content of the negative electrode binder in the sub-material layer closest to the current collector. This setting achieves the following effects: reducing ion transport impedance, mitigating the problem of negative electrode binder floating on the side closer to the current collector during high-speed mass production coating, which leads to kinetic degradation on the side farther from the current collector, and reducing the risk of insufficient adhesion on the side closer to the negative electrode current collector.
[0115] In some embodiments, the mass content of the negative electrode binder in the sub-material layer is greater than 0 and less than 4%, including but not limited to 0.5%, 1%, 2%, 2.5%, 3%, or 4%. The mass content of the negative electrode binder in the sub-material layer within the above range ensures that the negative electrode material layer has good adhesion performance and structural integrity, while avoiding adverse effects on the battery's electrochemical performance.
[0116] In some embodiments, the negative electrode material layer has at least one of the following characteristics:
[0117] e) When N ≥ 3, P1 ≦ P i+1 ≦P N Where 2≦i+1≦N-1;
[0118] f)2≦P N ≤4;
[0119] g)0<P1≦2.5;
[0120] h)P1 to P N Gradual increase, gradient increase, or step-like increase are all possible options, with gradient increase being the preferred choice.
[0121] i) In each of the sub-material layers, the first graphite, the second graphite, and the negative electrode binder are all uniformly distributed;
[0122] j) The negative electrode binder includes, but is not limited to, at least one of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), styrene-acrylic emulsion, carboxymethyl cellulose (CMC).
[0123] It is understandable that:
[0124] The above e) defines that, except for the sub-material layer furthest from the current collector and the sub-material layer closest to the current collector, the mass content of the negative electrode binder in the remaining sub-material layers can be equal to, equal to, or between the mass content of the negative electrode binder in the sub-material layer furthest from the current collector and the sub-material layer closest to the current collector. In this case, along the direction close to the surface of the current collector, P1 to P... N Gradual increase can be achieved through gradual increase, gradient increase, or step increase as described in h), with gradient increase being the preferred option. This setting can better achieve the following effects: reduce ion transport impedance, improve the problem of kinetic degradation on the side away from the current collector caused by the negative electrode binder floating on the side closer to the current collector during high-speed mass production coating, and reduce the risk of insufficient adhesion on the side closer to the negative electrode current collector.
[0125] It should be noted that in h) above, P1 to P N Gradual increase, gradient increase, and step increase are simply different trends from those mentioned above for R1 to R2. N The trends of change are gradually decreasing, gradient decreasing, and step increasing, which are opposite. However, the definitions of gradually increasing, gradient increasing, and step increasing are similar, so they will not be repeated here.
[0126] The above f)2≦P N ≦4 defines the range of the mass content of the negative electrode binder in the submaterial layer closest to the current collector. P NWithin the aforementioned range, a tight bond between the sub-material layer closest to the current collector and the current collector can be ensured, improving the overall structural stability. For example, P... N The values include, but are not limited to, 2%, 2.5%, 3%, 3.5%, or 4%.
[0127] The condition g)0 < P1 ≤ 2.5 defines the range of the mass content of the negative electrode binder in the sub-material layer furthest from the current collector. Within this range, P1 can reduce the obstruction to lithium-ion interface migration, thereby improving the rate performance and cycle activity of the battery. For example, values of P1 include, but are not limited to, 2.5%, 2.25%, 2%, 1.75%, 1.5%, 1.25%, 1%, 0.75%, 0.5%, or 0.25%.
[0128] As defined in i) above, the distribution of the first graphite, the second graphite, and the negative electrode binder in each of the sub-material layers is uniform, which indirectly defines that the mass ratio of the first graphite and the second graphite is equal at each position in each material layer, and the content of the negative electrode binder is equal. It should be noted that this is only an optional example. In the embodiments of this application, as needed and provided the preparation method is feasible, the first graphite, the second graphite, and the negative electrode binder in each of the sub-material layers can be distributed in any manner, such as linear continuous distribution, nonlinear continuous distribution, gradient distribution, step distribution, etc., along the direction close to the current collector surface.
[0129] In some implementations, 2≦N≦8, including but not limited to 2, 3, 4, 5, or 8. Within the above range, the number of sub-material layers in the negative electrode material layer can achieve gradient optimization of electrode performance, balancing fast charging, long cycling, and structural stability. More than 8 sub-material layers may have the following negative effects: the negative electrode sheet becomes inconvenient to prepare; the difficulty in controlling the thickness of each layer during coating increases significantly; problems such as interlayer mixing and uneven thickness are prone to occur, leading to a decrease in the consistency of electrode performance.
[0130] Further alternatively, 2≦N≦4, such as 3, etc.
[0131] As an optional example, the number of sub-material layers is 2, that is, N=2.
[0132] For example, when N is 2, 1≦R1≦4, including but not limited to 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8 or 3.9, etc., and can be selected as 7 / 3≦R1≦4.
[0133] For example, when N is 2, 1.5 ≦ P1 ≦ 2.5, including but not limited to 1.6, 1.7, 1.8, 1.9, 2.1, 2.2, 2.3 or 2.4, etc.
[0134] For example, when N is 2, 0 < R2 ≦ 1, including but not limited to 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, etc., and can be selected as 1 / 4 ≦ R2 ≦ 3 / 7.
[0135] For example, when N is 2, 2≦P2≦3, including but not limited to 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8 or 2.9, etc.
[0136] When there are two sub-material layers, the mass ratio of the first graphite to the second graphite and the content of the negative electrode binder in each sub-material layer are within the above range, which can achieve an efficient balance between fast charging performance and cycle stability while simplifying the production process.
[0137] As another alternative example, the number of sub-material layers is 3, that is, N=3.
[0138] For example, such as Figure 3 and Figure 4 As shown, the negative electrode includes a current collector 100 and a negative electrode material layer 200 disposed on at least a portion of the upper surface or the upper and lower surfaces of the current collector 100. The negative electrode material layer 200 includes a first sub-material layer 201, a second sub-material layer 202, and a third sub-material layer 203 sequentially stacked along a direction close to the surface of the current collector 100. The third sub-material layer 201 corresponds to the first sub-material layer, the second sub-material layer 202 corresponds to the second sub-material layer, and the third sub-material layer 203 corresponds to the third sub-material layer.
[0139] For example, when N is 3, 7 / 3≦R1≦4, including but not limited to 2.5, 2.8, 3.2, 3.6 or 4, etc.
[0140] For example, when N is 3, 1.5≦P1≦2.5, including but not limited to 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3 or 2.4, etc.
[0141] For example, when N is 3, 3 / 7≦R2≦7 / 3, including but not limited to 0.43, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2 or 2.3, etc.
[0142] For example, when N is 3, 1.8 ≦ P2 ≦ 2.8, including but not limited to 1.9, 2.0, 2.1, 2.2, 2.3, 2.3, 2.4, 2.5, 2.6 or 2.7, etc.
[0143] For example, when N is 3, 0 < R3 ≦ 3 / 7, including but not limited to 0.1, 0.15, 0.2, 0.25, 0.3, 0.35 or 0.4, etc.
[0144] For example, when N is 3, 2.1≦P3≦3.1, including but not limited to 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or 3, etc.
[0145] When there are three sub-material layers, the mass ratio of the first graphite to the second graphite and the content of the negative electrode binder in each sub-material layer are within the above range, which can achieve a gradient transition between lithium-ion transport rate and electrode structure stability, and further optimize the overall performance of the battery.
[0146] As another alternative example, the number of sub-material layers is 4, that is, N=4.
[0147] For example, when N is 4, 4≦R1≦6, including but not limited to 4.2, 4.5, 5, 5.5 or 6, etc.
[0148] For example, when N is 4, 1.5 ≦ P1 ≦ 2.1, including but not limited to 1.6, 1.7, 1.8, 1.9 or 2, etc.
[0149] For example, when N is 4, 3 / 2≦R2≦4, including but not limited to 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, or 3.9.
[0150] For example, when N is 4, 1.7 ≦ P2 ≦ 2.3, including but not limited to 1.8, 1.9, 2.0, 2.1 or 2.2, etc.
[0151] For example, when N is 4, 1 / 4≦R3≦3 / 2, including but not limited to 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3 or 1.4, etc.
[0152] For example, when N is 4, 1.9 ≦ P3 ≦ 2.5, including but not limited to 1.9, 2.0, 2.1, 2.2, 2.3, 2.3 or 2.4, etc.
[0153] For example, when N is 4, 0 < R4 ≦ 1 / 4, including but not limited to 0.1, 0.12, 0.15, 0.18, 0.2 or 0.23, etc.
[0154] For example, when N is 4, 2.2≦P4≦4, including but not limited to 2.2, 2.3, 2.4, 2.5, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8 or 3.9, etc.
[0155] When there are four sub-material layers, the mass ratio of the first graphite to the second graphite and the content of the negative electrode binder in each sub-material layer are within the above range, which can achieve more precise performance gradient control and enable the battery to achieve a higher level of synergy in terms of fast charging, cycle life, and safety.
[0156] In some approaches, when the number of sub-material layers is greater than four (i.e., N>4), the mass ratio gradient of the first graphite and the second graphite decreases while the mass content gradient of the negative electrode binder increases from the first side to the second side. Based on the gradient optimization of the mass ratio of the first graphite and the second graphite and the mass content of the negative electrode binder among different sub-material layers, the fast-charging performance and lifespan of the battery can be more precisely and flexibly controlled, reducing verification cycles and development costs, and improving product performance.
[0157] It should be noted that in the embodiments of this application, the first graphite exhibits good fast-charging performance, and the second graphite exhibits a long cycle life. There are no restrictions on the specific raw material selection, preparation method, fast-charging performance, or cycle life of the first and second graphite; they can be any raw material, preparation method, fast-charging performance standard, or long cycle life standard known in the art and suitable for use in secondary batteries, especially lithium-ion batteries. The first and second graphite can be manufactured in-house or obtained commercially.
[0158] For example, the interlayer spacing of the first graphite includes, but is not limited to, 0.3365nm, 0.3367nm, 0.3368nm, 0.3369nm, 0.3370nm, 0.3371nm, 0.3372nm, 0.3373nm, 0.3374nm, 0.3375nm, 0.3376nm, 0.3377nm, 0.3378nm, 0.3379nm, 0.3380nm, 0.3381nm, 0.3382nm, 0.3383nm, or 0.3384nm.
[0159] For example, the fast charging performance of the first graphite is required to meet the following standards: at room temperature of 25°C, at a 2C rate, the charging capacity reaches more than 80% of its rated capacity within 10 minutes, and at a 5C high-rate discharge, the capacity retention rate is not less than 70%.
[0160] For example, the interlayer spacing of the second graphite includes, but is not limited to, 0.3355nm, 0.3356nm, 0.3357nm, 0.3358nm, 0.3359nm, 0.3360nm, 0.3361nm, 0.3362nm, 0.3363nm, or 0.3364nm.
[0161] For example, the cycle life of the second graphite is required to meet the following standards: at room temperature of 25°C, under 1C charge-discharge cycle conditions, after 3000 cycles, the capacity retention rate is still not less than 80%, and the volume expansion rate during the cycle is controlled within 10%.
[0162] In the embodiments of this application, the interlayer spacing of the first graphite and the interlayer spacing of the second graphite can be obtained by detecting the 002 peak using X-ray diffraction phase analysis (XRD).
[0163] In some embodiments, the raw materials for preparing the first graphite include, but are not limited to, at least one of petroleum low-sulfur coke or needle coke. Using petroleum low-sulfur coke or needle coke as raw materials to prepare the first graphite can impart high crystallinity and an ordered layered structure to the graphite, which is beneficial for the rapid insertion and extraction of lithium ions, thereby improving its fast-charging performance.
[0164] In some embodiments, the sulfur content in the low-sulfur petroleum coke is less than 1 wt%, including but not limited to less than 0.9 wt%, less than 0.8 wt%, less than 0.7 wt%, less than 0.6 wt%, less than 0.5 wt%, less than 0.4 wt%, less than 0.3 wt%, less than 0.2 wt%, or less than 0.1 wt%. Preparing the first graphite from low-sulfur petroleum coke with elemental content within the above range can effectively reduce the side reactions generated by sulfur in the graphite during charging and discharging, and reduce the rate of increase in battery internal resistance.
[0165] For example, the preparation method of the first graphite includes: crushing low-sulfur petroleum coke or needle coke and then calcining it at high temperature (calcination temperature is 1200-1500℃) to remove volatiles and impurities; then performing graphitization treatment (graphitization temperature is 2800-3000℃) to improve crystallinity; and finally pulverizing and classifying to obtain first graphite particles with uniform particle size distribution (D50 is 10-20μm).
[0166] For example, in the above-mentioned method for preparing the first graphite, the calcination temperature includes, but is not limited to, 1250℃, 1300℃, 1350℃, 1400℃ or 1450℃.
[0167] For example, in the above-mentioned method for preparing the first graphite, the graphitization temperature includes, but is not limited to, 2850℃, 2900℃ or 2950℃.
[0168] For example, in the above-described method for preparing the first graphite, D50 includes, but is not limited to, 12 μm, 15 μm, or 17.5 μm.
[0169] In some embodiments, the raw materials for preparing the second graphite include, but are not limited to, at least one of petroleum sulfur coke or needle coke. Using petroleum sulfur coke or needle coke as raw materials to prepare the second graphite can suppress interlayer delamination during charge-discharge cycles, thereby improving its cycle stability.
[0170] In some embodiments, the sulfur content in the petroleum-derived sulfur coke is 1-5 wt%, including but not limited to 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, or 4.5 wt%. Preparing a second graphite from petroleum-derived sulfur coke with elemental content within the above range can suppress the growth of lithium dendrites and improve battery safety.
[0171] For example, the preparation method of the second graphite includes: crushing sulfur coke or needle coke in petroleum and then calcining it at a medium temperature (calcination temperature of 800-1000℃) to retain some sulfur elements and remove volatile impurities; then performing low-temperature graphitization treatment (graphitization temperature of 2000-2500℃) to ensure a certain degree of crystallinity while uniformly doping sulfur elements into the graphite interlayer; subsequently ball milling and shaping to control the particle morphology; and finally, classifying to obtain second graphite particles that meet the particle size requirements.
[0172] For example, in the above-mentioned method for preparing the second graphite, the calcination temperature includes, but is not limited to, 850°C, 900°C, or 950°C.
[0173] For example, in the above-mentioned method for preparing the second graphite, the graphitization temperature includes, but is not limited to, 2050℃, 2100℃, 2150℃, 2200℃, 2250℃, 2300℃, 2350℃, 2400℃ or 2450℃.
[0174] In some embodiments, the first graphite has at least one of the following characteristics:
[0175] (1) The particle size of Dv50 is 9-16μm;
[0176] (2) The particle size of Dv99 is below 65μm;
[0177] (3) The specific surface area of BET is 0.95-1.45㎡ / g.
[0178] For example, the Dv50 particle size of the first graphite includes, but is not limited to, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm.
[0179] For example, the Dv99 particle size of the first graphite includes, but is not limited to, less than 60 μm, less than 55 μm, less than 50 μm, less than 45 μm, less than 40 μm, less than 38 μm, less than 35 μm, less than 32 μm, less than 30 μm, less than 27 μm, less than 25 μm, less than 22 μm, less than 20 μm, or less than 15 μm.
[0180] The first graphite has a Dv50 and Dv99 particle size within the above range, which can reduce the migration distance of lithium ions inside the graphite particles, improve the lithium ion diffusion rate, and avoid the local polarization phenomenon caused by large particles, making the battery more stable during high-rate charging and discharging.
[0181] For example, the BET specific surface area of the first graphite includes, but is not limited to, 1 m² / g, 1.05 m² / g, 1.1 m² / g, 1.15 m² / g, 1.2 m² / g, 1.25 m² / g, 1.3 m² / g, 1.35 m² / g, or 1.4 m² / g. A BET specific surface area within the above range can provide sufficient lithium-ion insertion / extraction active sites, while avoiding excessive electrolyte consumption and increased side reactions caused by an excessively large specific surface area.
[0182] In some embodiments, the second graphite has at least one of the following characteristics:
[0183] (1) The particle size of Dv50 is 11-18 μm;
[0184] (2) The particle size of Dv99 is below 80 μm;
[0185] (3) The specific surface area of BET is 0.8-1.3㎡ / g.
[0186] For example, the Dv50 particle size of the second graphite includes, but is not limited to, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm or 17μm.
[0187] For example, the Dv99 particle size of the second graphite includes, but is not limited to, less than 75 μm, less than 70 μm, less than 65 μm, less than 60 μm, less than 55 μm, less than 50 μm, less than 45 μm, less than 43 μm, less than 40 μm, less than 38 μm, less than 35 μm, less than 32 μm, less than 30 μm, less than 27 μm, less than 25 μm, less than 22 μm, less than 20 μm, or less than 15 μm.
[0188] The second type of graphite has Dv50 and Dv99 particle sizes within the above range, which can reduce the contact area with the electrolyte, thereby reducing the occurrence of side reactions. At the same time, the larger particle structure can better resist the stress caused by volume expansion during cycling, thus improving structural stability.
[0189] For example, the BET specific surface area of the second graphite includes, but is not limited to, 0.9 m² / g, 1 m² / g, 1.05 m² / g, 1.1 m² / g, 1.15 m² / g, 1.2 m² / g, 1.25 m² / g, or 1.3 m² / g. With a BET specific surface area within the above range, the surface active sites can be minimized while ensuring the basic lithium-ion transport requirements, thereby reducing the risk of electrolyte decomposition and lithium dendrite growth.
[0190] In some embodiments, the Dv50 particle size of the second graphite is larger than that of the first graphite.
[0191] In some embodiments, the Dv99 particle size of the second graphite is larger than that of the first graphite.
[0192] In some embodiments, the BET specific surface area of the second graphite is smaller than that of the first graphite.
[0193] The second graphite has larger Dv50 and Dv99 particle sizes than the first graphite, and its BET specific surface area is smaller than that of the first graphite, thus achieving complementary properties between the two graphite materials.
[0194] In the embodiments of this application, the preparation method of the negative electrode sheet is not limited, and can be any negative electrode sheet preparation method known in the art for secondary batteries, especially lithium-ion batteries.
[0195] For example, the preparation method of the negative electrode sheet is as follows: the first graphite, the second graphite, the negative electrode binder and the negative electrode conductive agent are respectively prepared into slurries for each sub-material layer according to a preset ratio, and the slurries are coated onto the current collector in sequence through a multi-layer coating process. After drying and rolling, the negative electrode sheet is obtained.
[0196] For example, the negative electrode conductive agent has a mass content greater than 0 and less than 2% in the sub-material layer, such as 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, or 1.8%.
[0197] In the embodiments of this application, the specific selection of the negative electrode conductive agent is not limited, and it can be any negative electrode conductive agent known in the art for use in secondary batteries, especially lithium-ion batteries.
[0198] <Positive Electrode>
[0199] The positive electrode sheet of this application embodiment includes a positive electrode material, and the positive electrode material includes a positive electrode lithium supplement.
[0200] Adding a positive electrode lithium replenisher to the positive electrode provides additional active lithium to the negative electrode during the first charge, replenishing the active lithium consumed during cycling and storage, thus improving cycle life and calendar life. Simultaneously, the positive electrode lithium replenisher releases oxygen at high potential, increasing the inorganic component content in the negative electrode SEI film. After the material phase transition, volume shrinkage increases the positive electrode porosity, reduces ion transport impedance, and enhances fast charging capability.
[0201] In some embodiments, the positive electrode lithium replenishing agent includes, but is not limited to, at least one of lithium-rich lithium iron ore (LFO) and lithium-rich lithium nickel ore (LNO).
[0202] In some embodiments, the positive electrode lithium replenisher has a mass content of 0.5-5% in the positive electrode material, including but not limited to 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, or 4.5%. Having the positive electrode lithium replenisher within this range can better achieve the following effects: providing additional active lithium to the negative electrode during the first charge, replenishing the active lithium consumed during cycling and storage, and improving cycle life and calendar life. Simultaneously, the positive electrode lithium replenisher releases oxygen at high potential, increasing the inorganic component content in the negative electrode SEI film; the volume shrinkage after the material phase transition increases the positive electrode porosity, reduces ion transport impedance, and improves fast charging capability.
[0203] In some embodiments, the cathode material further includes a cathode active material, which includes, but is not limited to, at least one of lithium iron phosphate (LFP) and ternary materials (NCM).
[0204] For example, the ternary material includes, but is not limited to, ternary cathode materials containing nickel, cobalt and manganese.
[0205] For example, the chemical formula of the ternary material is: LiNi x Co γ Mn z O2, where x + y + z = 1, and x, y, and z are all numbers greater than 0. Specifically, this may include, but is not limited to, LiNi. 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.9 Co 0.05 Mn 0.05O2, etc.
[0206] In some embodiments, when the positive electrode active material is lithium iron phosphate, the upper limit voltage of the secondary battery is below 3.8V (≤3.8V), including but not limited to below 3.7V, below 3.6V, below 3.5V, below 3.4V, below 3.3V, below 3.2V, below 3.1V, or below 3V. When the positive electrode active material is lithium iron phosphate, the upper limit voltage of the secondary battery is controlled within the above range to ensure the cycle stability of the battery.
[0207] In some embodiments, when the positive electrode active material is lithium iron phosphate, the risk of gas generation during positive electrode lithium replenishment is relatively low. The positive electrode lithium replenishing agent is lithium-rich lithium iron phosphate and lithium-rich lithium nickel phosphate, and the mass ratio of lithium-rich lithium iron phosphate to lithium-rich lithium nickel phosphate is c, 1≤c≤5, including but not limited to 1.1, 1.2, 1.3, 1.4, 1.5, 1.75, 2, 2.25, 2.5, 2.75, 3, 3.25, 3.5, 3.75, 4, 4.25, 4.5, or 4.75. When the positive electrode active material is lithium iron phosphate, the mass ratio of lithium-rich lithium iron phosphate to lithium-rich lithium nickel phosphate within the above range can fully utilize the synergistic effect of the two lithium replenishing agents, improving lithium replenishment efficiency and energy density.
[0208] In some embodiments, when the positive electrode active material is the ternary material, the upper limit voltage of the secondary battery is 4.2-4.5V, including but not limited to 4.2V, 4.3V, 4.4V, 4.45V, or 4.5V. When the positive electrode active material is the ternary material, controlling the upper limit voltage of the secondary battery within the above range allows for full utilization of the high capacity characteristics of the ternary material while ensuring battery safety.
[0209] In some embodiments, when the positive electrode active material is the ternary material, the positive electrode lithium replenishment gas production is relatively large. The positive electrode lithium replenishing agent is the lithium-rich lithium iron ferrite and the lithium-rich lithium nickel ferrite, and the mass ratio of the lithium-rich lithium iron ferrite and the lithium-rich lithium nickel ferrite is d, 0 < d ≤ 1, including but not limited to 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or 0.9. When the positive electrode active material is the ternary material, the mass ratio of the lithium-rich lithium iron ferrite and the lithium-rich lithium nickel ferrite within the above range can meet the usage requirements of ternary materials at higher voltages, reducing the risk of gas production while maintaining the lithium replenishment effect.
[0210] In some embodiments, the positive electrode material further includes a positive electrode binder.
[0211] This embodiment does not limit the specific selection of the positive electrode binder. It can be any positive electrode binder known in the art for secondary batteries, especially lithium-ion batteries, such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), etc.
[0212] In some embodiments, the positive electrode material further includes a positive electrode conductive agent.
[0213] This embodiment does not limit the specific selection of the positive electrode conductive agent. It can be any positive electrode conductive agent known in the art for use in secondary batteries, especially lithium-ion batteries, such as conductive carbon black (Super-P), graphene, etc.
[0214] In some embodiments, the positive electrode active material has a mass content of 90-96% in the positive electrode material, including but not limited to 91-96%, and including but not limited to 92%, 93%, 94% or 95%.
[0215] In some embodiments, the positive electrode conductive agent and the positive electrode binder each independently have a mass content of 2-5% in the positive electrode material, including but not limited to 2.5%, 3%, 3.5%, 4% or 4.5%.
[0216] It should be noted that in the embodiments of this application, the total mass content of each component of the cathode material is 100%.
[0217] Secondary batteries
[0218] The secondary battery of this application embodiment includes the above-mentioned positive electrode, negative electrode and separator, wherein the negative electrode is the negative electrode of this application embodiment.
[0219] In some implementations, the secondary battery includes lithium-ion batteries, etc.
[0220] It should be noted that the embodiments of this application do not limit the specifications of the positive electrode sheet, the specific selection and specifications of the separator, etc., and can be any positive electrode sheet, separator, etc., known in the art for secondary batteries, especially lithium-ion batteries.
[0221] The secondary battery of this application embodiment can bring at least the following beneficial effects:
[0222] 1. Introducing a positive electrode lithium replenishment scheme provides additional active lithium to compensate for the active lithium consumed during cycling and storage, thus extending the lifespan. Simultaneously, the volume shrinkage of the lithium replenishment material during the first charge (formation) process increases the porosity of the positive electrode, and the oxygen release reacts with the electrolyte to increase the proportion of inorganic components in the negative electrode SEI film, reducing lithium-ion transport impedance and improving kinetic performance.
[0223] 2. Negative Electrode Design – In the multiple sub-material layers of the negative electrode material layer, the first graphite and the second graphite are mixed, and the mass ratio (R1) of the first graphite and the second graphite in the sub-material layer farthest from the current collector is limited to being higher than their mass ratio (R2) in the sub-material layer closest to the current collector. N (For example, gradient design) Compared to related technologies where different types of graphite are used in the upper and lower layers (the upper layer being the one furthest from the current collector and the lower layer being the one closest to the current collector), this approach can reduce lithium-ion concentration polarization caused by sudden changes in kinetics and porosity differences along the thickness direction, thereby improving fast-charging performance and reducing the risk of lithium plating. Simultaneously, controlling the content of the sub-material layer furthest from the current collector to be lower than that in the sub-material layer closest to the current collector (e.g., gradient design) can reduce ion transport impedance, improve the problem of negative electrode binder floating on the side closest to the current collector during high-speed mass production coating, which leads to kinetic degradation on the side furthest from the current collector, and reduce the risk of insufficient adhesion on the side closest to the negative electrode and current collector.
[0224] <Electrical Appliances>
[0225] The electrical device in the embodiments of this application includes the secondary battery in the embodiments of this application.
[0226] In some embodiments, the electrical device includes a vehicle, lighting device, electronic device, etc., and may be a vehicle.
[0227] The electrical device of this application embodiment has at least the beneficial effects of the negative electrode plate, secondary battery, etc. of this application embodiment.
[0228] The following non-limiting embodiments further illustrate certain features of the present technology.
[0229] I. Examples and Comparative Examples
[0230] The method for preparing the first graphite includes: crushing low-sulfur petroleum coke or needle coke and then calcining it at high temperature (calcination temperature is 1200-1500℃) to remove volatiles and impurities; then performing graphitization treatment (graphitization temperature is 2800-3000℃) to improve crystallinity; and finally pulverizing and classifying to obtain first graphite particles with uniform particle size distribution (D50 is 10-20μm).
[0231] The method for preparing the second graphite includes: crushing petroleum sulfur coke or needle coke and then calcining it at a medium temperature (calcination temperature of 800-1000℃) to retain some sulfur elements and remove volatile impurities; then performing low-temperature graphitization treatment (graphitization temperature of 2000-2500℃) to ensure a certain degree of crystallinity while uniformly doping sulfur elements into the graphite interlayer; subsequently, ball milling and shaping to control the particle morphology; and finally, classification to obtain second graphite particles that meet the particle size requirements.
[0232] The first and second graphite involved in each embodiment and comparative example were prepared according to the above method, and the first and second graphite involved in each embodiment and comparative example are shown in Table 1.
[0233] Table 1 First Graphite and Second Graphite
[0234]
[0235]
[0236] Note: In Table 1, " / " indicates that it does not involve sulfur or the sulfur content is 0; A, B, C, D, and E are only used to distinguish different types of graphite and have no special meaning. For example, first graphite A and first graphite B represent two different types of first graphite that meet the requirements of Table 1.
[0237] Example 1
[0238] (Negative electrode plate)
[0239] The negative electrode sheet in this embodiment includes a current collector and negative electrode material layers disposed on opposite side surfaces of the current collector; the negative electrode material layers include a first sub-material layer and a second sub-material layer sequentially stacked along a direction close to the surface of the current collector. Wherein:
[0240] The current collector is a copper foil with a thickness of 7 micrometers.
[0241] The first sub-material layer is composed of the following components by mass percentage: 96.3% negative electrode active material, 2.5% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material consists of first graphite and second graphite, with a mass ratio of 7:3. The first graphite is designated as First Graphite A, and the second graphite as Second Graphite A. The negative electrode binder is composed of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1. The negative electrode conductive agent is conductive carbon black (SuperP).
[0242] The second sub-material layer is composed of the following components by mass percentage: 95.8% negative electrode active material, 3% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material consists of first graphite and second graphite, with a mass ratio of 3:7. The first graphite is designated as First Graphite A, and the second graphite as Second Graphite A. The negative electrode binder is composed of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1. The negative electrode conductive agent is conductive carbon black (Super P).
[0243] The method for preparing the negative electrode sheet in this embodiment is as follows: slurries for the first sub-material layer and the second sub-material layer are prepared separately. For the first sub-material layer, first graphite A, second graphite A, PAA, SBR, CMC, and Super P are weighed according to the above-mentioned mass ratio. The negative electrode active material is added to deionized water and stirred at high speed for 1 hour until uniformly mixed. Then, the negative electrode binder is added, and stirring is continued for 2 hours to form a uniform slurry with a solid content of 45%. For the second sub-material layer, first graphite A, second graphite A, PAA, SBR, CMC, and Super P are weighed according to the above-mentioned mass ratio. The negative electrode active material is added to deionized water and stirred at high speed for 1 hour until uniformly mixed. Then, the negative electrode binder is added, and stirring is continued for 2 hours to form a uniform slurry with a solid content of 48%. First, a second sub-material layer slurry is evenly coated onto both opposite surfaces of the copper foil, with a coating thickness controlled at 80 μm. After pre-drying in an 80℃ oven for 10 minutes, a first sub-material layer slurry is then coated on top, with a coating thickness of 50 μm. The coated foil is then placed in a 120℃ vacuum drying oven for 2 hours to remove residual moisture. The dried electrode is then subjected to roller pressing to control the total compaction density to 1.6 g / cm³. 3 Finally, the electrode is slit and sheeted to obtain the negative electrode sheet.
[0244] (Positive electrode sheet)
[0245] The positive electrode sheet of this embodiment includes a current collector and positive electrode material layers disposed on two opposing surfaces of the current collector. The positive electrode material layer is composed of the following components by mass percentage: 96% positive electrode active material, 2% positive electrode conductive agent, and 2% positive electrode binder. Wherein:
[0246] The current collector is an aluminum foil with a thickness of 12 micrometers, the positive electrode active material is lithium iron phosphate (LFP), the positive electrode conductive agent is conductive carbon black (Super P), and the positive electrode binder is polyvinylidene fluoride (PVDF).
[0247] The method for preparing the positive electrode sheet in this embodiment includes: mixing the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder with the solvent N-methylpyrrolidone (NMP) to form a positive electrode slurry. The obtained positive electrode slurry is uniformly coated on both opposite surfaces of an aluminum foil current collector, dried at 85°C, cold-pressed, cut, and slit to obtain a positive electrode sheet with a compaction density of 3.45 g / cc (cubic centimeters).
[0248] Example 2
[0249] This embodiment is basically the same as embodiment 1, except that:
[0250] In the positive electrode sheet, the positive electrode material layer is composed of the following components by mass percentage: 94.08% positive electrode active material, 1.92% positive electrode lithium supplement, 2% positive electrode conductive agent, and 2% positive electrode binder. The positive electrode lithium supplement is composed of lithium-rich lithium iron ferrite (LFO) and lithium-rich lithium nickel ferrite (LNO) in a mass ratio of 8:2.
[0251] In the preparation method of the positive electrode sheet, the positive electrode active material, positive electrode lithium supplement, positive electrode conductive agent and positive electrode binder are mixed with the solvent N-methylpyrrolidone (NMP) to form a positive electrode slurry.
[0252] Example 3
[0253] (Negative electrode plate)
[0254] like Figure 4 As shown, the negative electrode sheet in this embodiment includes a current collector 100, and a negative electrode material layer 200 is provided on both the upper and lower surfaces of the current collector 100; the negative electrode material layer 200 includes a first sub-material layer 201, a second sub-material layer 202, and a third sub-material layer 203 sequentially stacked along a direction close to the surface of the current collector 100. Wherein:
[0255] The current collector 100 is a copper foil with a thickness of 7 micrometers.
[0256] The first submaterial layer 201 is composed of the following components by mass percentage: 96.3% negative electrode active material, 2.5% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material consists of first graphite and second graphite, with a mass ratio of 7:3. The first graphite is designated as first graphite A, and the second graphite as second graphite A. The negative electrode binder consists of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1. The negative electrode conductive agent is conductive carbon black (SuperP).
[0257] The material of the second sub-material layer 202 is composed of the following components by mass percentage: 96.1% negative electrode active material, 2.7% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material consists of first graphite and second graphite, with a mass ratio of 5:5. The first graphite is designated as first graphite A, and the second graphite as second graphite A. The negative electrode binder consists of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1. The negative electrode conductive agent is conductive carbon black (SuperP).
[0258] The third submaterial layer 203 is composed of the following components by mass percentage: 95.8% negative electrode active material, 3% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material consists of first graphite and second graphite, with a mass ratio of 3:7. The first graphite is designated as first graphite A, and the second graphite as second graphite A. The negative electrode binder consists of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1. The negative electrode conductive agent is conductive carbon black (Super P).
[0259] The method for preparing the negative electrode sheet in this embodiment is as follows: slurries for the first sub-material layer 201, the second sub-material layer 202, and the third sub-material layer 203 are prepared respectively. First graphite A, second graphite A, PAA, SBR, CMC, and Super P are weighed according to the mass ratio of each sub-material layer. The negative electrode active material of each layer is added to deionized water and stirred at high speed for 1.5 hours until uniformly mixed. Then, the corresponding proportion of negative electrode binder is added, and stirring continues for 2.5 hours. The solid content of the first sub-material layer slurry is controlled at 44%, the solid content of the second sub-material layer slurry is controlled at 46%, and the solid content of the third sub-material layer slurry is controlled at 49%. A third sub-material layer slurry, 60 μm thick, was coated on both the upper and lower surfaces of the copper foil and pre-dried at 85°C for 12 minutes. Next, a second sub-material layer slurry, 40 μm thick, was coated on top and pre-dried at 85°C for 12 minutes. Finally, a first sub-material layer slurry, 30 μm thick, was coated. The entire process was then dried in a 125°C vacuum drying oven for 2.5 hours. The dried electrode was then subjected to roll pressing to control the total compaction density to 1.55 g / cm³. 3 Then, the electrode is cut and sheeted to obtain the negative electrode sheet.
[0260] (Positive electrode sheet)
[0261] The positive electrode sheet of this embodiment includes a current collector and positive electrode material layers disposed on the upper and lower surfaces of the current collector. The positive electrode material layer is composed of the following components by mass percentage: 94.08% positive electrode active material, 1.92% positive electrode lithium supplement, 2% positive electrode conductive agent, and 2% positive electrode binder. The positive electrode lithium supplement is composed of lithium-rich lithium iron ferrite (LFO) and lithium-rich lithium nickel oxide (LNO), with a mass ratio of lithium-rich lithium iron ferrite (LFO) to lithium-rich lithium nickel oxide (LNO) of 8:2.
[0262] in:
[0263] The current collector is an aluminum foil with a thickness of 12 micrometers, the positive electrode active material is lithium iron phosphate (LFP), the positive electrode conductive agent is conductive carbon black (Super P), and the positive electrode binder is polyvinylidene fluoride (PVDF).
[0264] The method for preparing the positive electrode sheet in this embodiment includes: mixing a positive electrode active material, a positive electrode conductive agent, a positive electrode conductive agent and a positive electrode binder with the solvent N-methylpyrrolidone (NMP) to form a positive electrode slurry. The obtained positive electrode slurry is uniformly coated on the upper and lower surfaces of an aluminum foil current collector, dried at 85°C, cold-pressed, cut, and slit to obtain a positive electrode sheet with a compacted density of 3.45 g / cc (cubic centimeters).
[0265] Example 4
[0266] This embodiment is basically the same as embodiment 3, except that:
[0267] In the positive electrode, the positive active material is the ternary material NCM811 (LiNi). 0.8 Co 0.1 Mn 0.1 The mass ratio of lithium iron phosphate (LFO) to lithium nickel phosphate (LNO) is 2:8.
[0268] Example 5
[0269] This embodiment is basically the same as embodiment 1, except that:
[0270] In the positive electrode, the positive active material is the ternary material NCM811 (LiNi). 0.8 Co 0.1 Mn 0.1 O2).
[0271] Example 6 (Four-layer case)
[0272] (Negative electrode plate)
[0273] The negative electrode sheet in this embodiment includes a current collector and negative electrode material layers disposed on opposite sides of the current collector; the negative electrode material layers include a first sub-material layer, a second sub-material layer, a third sub-material layer, and a fourth sub-material layer stacked sequentially along a direction close to the surface of the current collector. Wherein:
[0274] The current collector is a copper foil with a thickness of 7 micrometers.
[0275] The first sub-material layer is composed of the following components by mass percentage: 96.7% negative electrode active material, 2.1% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material consists of first graphite and second graphite, with a mass ratio of 8:2. The first graphite is designated as First Graphite A, and the second graphite as Second Graphite A. The negative electrode binder is composed of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1. The negative electrode conductive agent is conductive carbon black (SuperP).
[0276] The second sub-material layer is composed of the following components by mass percentage: 96.5% negative electrode active material, 2.3% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material consists of first graphite and second graphite, with a mass ratio of 7:3. The first graphite is designated as First Graphite A, and the second graphite as Second Graphite A. The negative electrode binder is composed of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1. The negative electrode conductive agent is conductive carbon black (SuperP).
[0277] The third sub-material layer is composed of the following components by mass percentage: 96.3% negative electrode active material, 2.5% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material consists of first graphite and second graphite, with a mass ratio of 6:4. The first graphite is designated as First Graphite A, and the second graphite as Second Graphite A. The negative electrode binder is composed of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1. The negative electrode conductive agent is conductive carbon black (SuperP).
[0278] The fourth sub-material layer is composed of the following components by mass percentage: 94.8% negative electrode active material, 4% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material consists of first graphite and second graphite, with a mass ratio of 2:8. The first graphite is designated as First Graphite A, and the second graphite as Second Graphite A. The negative electrode binder consists of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1. The negative electrode conductive agent is conductive carbon black (Super P).
[0279] The method for preparing the negative electrode sheet in this embodiment is as follows: slurries for the first sub-material layer, the second sub-material layer, the third sub-material layer, and the fourth sub-material layer are prepared respectively. First graphite A, second graphite A, PAA, SBR, CMC, and Super P are weighed according to the mass ratio of each sub-material layer. The negative electrode active material of each layer is added to deionized water and stirred at high speed for 2 hours until uniformly mixed. Then, the corresponding proportion of negative electrode binder is added, and stirring continues for 3 hours. The solid content of the first sub-material layer slurry is controlled at 43%, the solid content of the second sub-material layer slurry is controlled at 45%, the solid content of the third sub-material layer slurry is controlled at 47%, and the solid content of the fourth sub-material layer slurry is controlled at 50%. A fourth sub-material layer slurry, 50 μm thick, is applied to both opposite surfaces of the copper foil and pre-dried at 90°C for 15 minutes. Next, a third sub-material layer slurry, 40 μm thick, is applied and pre-dried at 90°C for 15 minutes. A second sub-material layer slurry, 30 μm thick, is then applied and pre-dried at 90°C for 15 minutes. Finally, a first sub-material layer slurry, 25 μm thick, is applied. After completion, the electrode is dried in a 130°C vacuum drying oven for 3 hours to remove residual moisture. The dried electrode is then rolled to achieve a total compaction density of 1.5 g / cm³. 3 Then, the electrode is cut and sheeted to obtain the negative electrode sheet.
[0280] (Positive electrode sheet)
[0281] The positive electrode sheet of this embodiment includes a current collector and positive electrode material layers disposed on two opposing surfaces of the current collector. The positive electrode material layer is composed of the following components by mass percentage: 94.08% positive electrode active material, 1.92% positive electrode lithium supplement, 2% positive electrode conductive agent, and 2% positive electrode binder. The positive electrode lithium supplement is composed of lithium-rich lithium iron ferrite (LFO) and lithium-rich lithium nickel oxide (LNO), with a mass ratio of lithium-rich lithium iron ferrite (LFO) to lithium-rich lithium nickel oxide (LNO) of 8:2.
[0282] in:
[0283] The current collector is an aluminum foil with a thickness of 12 micrometers, the positive electrode active material is lithium iron phosphate (LFP), the positive electrode conductive agent is conductive carbon black (Super P), and the positive electrode binder is polyvinylidene fluoride (PVDF).
[0284] The method for preparing the positive electrode sheet in this embodiment includes: mixing a positive electrode active material, a positive electrode conductive agent, a positive electrode conductive agent and a positive electrode binder with the solvent N-methylpyrrolidone (NMP) to form a positive electrode slurry. The obtained positive electrode slurry is uniformly coated on both opposite surfaces of a thick aluminum foil current collector, dried at 85°C, cold-pressed, cut, and slit to obtain a positive electrode sheet with a compacted density of 3.45 g / cc (cubic centimeters).
[0285] Example 7
[0286] This embodiment is basically the same as embodiment 6, except that:
[0287] In the positive electrode, the positive active material is the ternary material NCM811 (LiNi). 0.8 Co 0.1 Mn 0.1 O2).
[0288] Examples 8-15 are basically the same as Example 1, except that some substances are selected and parameter values are different, as shown in Table 2.
[0289] Table 2. Selection of some substances and parameter values in Examples 8-15
[0290]
[0291]
[0292] Examples 16-23 are basically the same as Example 4, except that some substances are selected and parameter values are different, as shown in Table 3.
[0293] Table 3. Selection of some substances and parameter values in Examples 16-23
[0294]
[0295]
[0296] Note: In Table 3, the increase or decrease in the content of the positive electrode lithium supplement compared to Example 4 is uniformly incorporated into the positive electrode active material of the corresponding example. Taking Example 22 as an example, the mass content of the positive electrode lithium supplement in the positive electrode material is 0.5%, which is 1.42% less than that in Example 4. After the reduced 1.42% is uniformly incorporated into the positive electrode active material, the mass content of the positive electrode active material in the positive electrode material changes from 94.08% in Example 4 to 95.5%.
[0297] Examples 24-25 are basically the same as Example 6, except that some parameter values are different, as shown in Table 4.
[0298] Table 4. Parameter values for Examples 6 and 24-25
[0299]
[0300] Example 26 (The mass ratio of the two lithium supplements is intermediate compared to Example 2)
[0301] This embodiment is basically the same as embodiment 2, except that:
[0302] In the positive electrode, the mass ratio of lithium iron phosphate (LFO) to lithium nickel phosphate (LNO) is 3:1.
[0303] Comparative Example 1
[0304] This comparative example is basically the same as Example 1, except that:
[0305] In the negative electrode plate:
[0306] The first sub-material layer is composed of the following components by mass percentage: 96.3% negative electrode active material, 2.5% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material is first graphite, specifically first graphite A; the negative electrode binder is composed of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1; the negative electrode conductive agent is conductive carbon black (Super P).
[0307] The second sub-material layer is composed of the following components by mass percentage: 95.8% negative electrode active material, 3% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material is second graphite, specifically second graphite A. The negative electrode binder is composed of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1. The negative electrode conductive agent is conductive carbon black (Super P).
[0308] Comparative Example 2
[0309] This comparative example is basically the same as Example 2, except that:
[0310] In the negative electrode plate:
[0311] The first sub-material layer is composed of the following components by mass percentage: 96.3% negative electrode active material, 2.5% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material is first graphite, specifically first graphite A; the negative electrode binder is composed of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1; the negative electrode conductive agent is conductive carbon black (Super P).
[0312] The second sub-material layer is composed of the following components by mass percentage: 95.8% negative electrode active material, 3% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material is second graphite, specifically second graphite A. The negative electrode binder is composed of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC = 1:1:1. The negative electrode conductive agent is conductive carbon black (Super P).
[0313] Comparative Example 3
[0314] This comparative example is basically the same as Example 5, except that:
[0315] In the negative electrode plate:
[0316] The first sub-material layer is composed of the following components by mass percentage: 96.3% negative electrode active material, 2.5% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material is first graphite, which is first graphite A; the negative electrode binder is composed of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC of 1:1:1.
[0317] The second sub-material layer is composed of the following components by mass percentage: 95.8% negative electrode active material, 3% negative electrode binder, and 1.2% negative electrode conductive agent. The negative electrode active material is second graphite, specifically second graphite A. The negative electrode binder is composed of polyacrylic acid (PAA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC), with a mass ratio of PAA:SBR:CMC of 1:1:1.
[0318] Comparative Example 4
[0319] This comparative example is basically the same as Example 1, except that:
[0320] In the negative electrode sheet, the mass ratio of the first graphite and the second graphite in the first sub-material layer is 3:7, and the mass ratio of the first graphite and the second graphite in the second sub-material layer is 7:3.
[0321] Comparative Example 5
[0322] This comparative example is basically the same as Example 1, except that:
[0323] In the negative electrode sheet, the mass ratio of the first graphite in the first sub-material layer and the second graphite in the second sub-material layer is 7:3.
[0324] II. Performance Testing
[0325] The positive and negative electrode sheets of each embodiment and comparative example were assembled into lithium-ion batteries, and their respective electrochemical performance was tested.
[0326] in:
[0327] The method for preparing a lithium-ion battery includes the following steps:
[0328] (1) Selection of the isolation membrane: The isolation membrane is selected to be a polyethylene (PE) isolation membrane with a thickness of 7 micrometers.
[0329] (2) Assemble the bare cell: Stack the positive electrode sheet, separator, negative electrode sheet, and separator obtained in each embodiment or comparative example in sequence, so that the separator is in the middle of the positive and negative electrodes to play the role of isolation. Then, wind it up and attach the tail tape at the winding point to obtain the bare cell.
[0330] (3) Electrolyte preparation: Ethyl carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed organic solvent. Then, fully dried lithium hexafluorophosphate (LiPF6) is dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0331] (4) Assemble lithium-ion batteries: The bare cells are placed into an aluminum shell, dried at 100°C, and then injected with the prepared electrolyte. After vacuum sealing, settling, formation, shaping and other processes, the lithium-ion battery is prepared.
[0332] Electrochemical performance includes fast charging performance, cycle performance, and storage performance.
[0333] The fast-charging performance test method is as follows: A fully charged lithium-ion battery (charged at a constant current rate of 0.5C to the cutoff voltage, then charged at a constant voltage rate of the cutoff voltage until the current ≤0.05C) is discharged at a constant current rate of 0.5C to the cutoff voltage in an environment of 25℃±2℃, and the discharge capacity is recorded as the rated capacity. Subsequently, the battery is discharged to a depleted state (discharged at a constant current rate of 0.5C to the cutoff voltage), and then charged at constant current rates of 2C, 3C, and 5C to the cutoff voltage. The capacity at 10 minutes, 15 minutes, and 20 minutes of charging is recorded, and the percentage of this capacity to the rated capacity is calculated to evaluate the fast-charging capability at different rates. During the test, the battery casing temperature must be kept below 45℃. If it exceeds this temperature, the test is paused and restarted after the temperature drops below 30℃.
[0334] The cycle performance test method is as follows: The lithium-ion battery is subjected to charge-discharge cycle tests at 25℃±2℃. The charging process is as follows: constant current charging at a 1C rate to the cutoff voltage, followed by constant voltage charging at the cutoff voltage until the current ≤0.05C. The discharging process is as follows: constant current discharging at a 1C rate to the cutoff voltage. After every 100 cycles, the discharge capacity of that cycle is recorded, and the percentage of that capacity relative to the first cycle discharge capacity (capacity retention rate) is calculated. When the capacity retention rate drops to 80%, the cycle test is stopped, and the number of cycles is recorded. If the capacity retention rate is still above 80% after 3000 cycles, the test is stopped, and the capacity retention rate at this point is recorded.
[0335] The storage performance test method is as follows: The lithium-ion battery is charged to full capacity at a 0.5C rate, left to stand at 25℃±2℃ for 24 hours, and then discharged at a 0.5C rate to the cutoff voltage. The discharge capacity (initial capacity) is recorded. The battery is then fully charged again and stored at 25℃±2℃, 45℃±2℃, and 60℃±2℃ for 30 days, 90 days, and 180 days, respectively. After storage, the battery is transferred to a 25℃±2℃ environment and left to stand for 24 hours. It is then discharged at a 0.5C rate to the cutoff voltage, and the discharge capacity (post-storage capacity) is recorded. The capacity retention rate is calculated as (post-storage capacity / initial capacity × 100%). Afterward, the battery is charged to full capacity again at a 0.5C rate, left to stand for 24 hours, and then discharged at a 0.5C rate. The recovered capacity is recorded, and the capacity recovery rate is calculated as (recovered capacity / initial capacity × 100%).
[0336] The electrochemical performance test results are shown in Table 4.
[0337] Table 4 Electrochemical performance test results
[0338]
[0339]
[0340] Referring to Table 4:
[0341] Under the same conditions, the lithium-ion batteries corresponding to the negative electrode sheets of each embodiment of this application have at least better fast charging performance and cycle performance than the lithium-ion batteries corresponding to the negative electrode sheets of the comparative examples.
[0342] Comparing Example 1 with Comparative Example 1, Example 2 with Comparative Example 2, and Example 5 with Comparative Example 3, it can be seen that in the negative electrode sheet of this application, the mass ratio of the first graphite and the second graphite on the side away from the current collector is greater than that on the side closer to the current collector. Compared to the cases in Comparative Examples 1-3 where the negative electrode active material on the side closer to the current collector is entirely second graphite and the negative electrode active material on the side away from the current collector is entirely first graphite, the fast charging performance and cycle performance are improved, and the charging time from 10-80% SOC is reduced by at least 1 minute. In addition, Example 5 also shows a significant improvement in battery storage performance compared to Comparative Example 3.
[0343] Comparing Example 1, Comparative Example 4, and Comparative Example 5, it can be seen that when the mass ratio distribution of the first graphite and the second graphite in the negative electrode material layer does not meet the requirements of this application (the side farther from the current collector is greater than the side closer to the current collector), the lithium-ion transport efficiency is low, the structural stability is poor, and the active lithium is severely lost and the capacity decay is accelerated during long-term cycling and high-temperature storage.
[0344] In this application, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0345] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0346] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.
Claims
1. A negative electrode sheet, characterized in that, include: current collector; A negative electrode material layer is disposed on at least a portion of at least one surface of the current collector. The negative electrode material layer comprises N sub-material layers stacked along a direction close to the surface of the current collector, where N ≥ 2. The sub-material layers comprise a first graphite and a second graphite, wherein the interlayer spacing of the first graphite is a nm and the interlayer spacing of the second graphite is b nm, and a and b satisfy: 0.3365 ≤ a ≤ 0.3385, 0.3355 ≤ b < 0.3365. Define R as the mass ratio of the first graphite to the second graphite in the i-th submaterial layer along the direction close to the surface of the current collector. i If 1 ≦ i ≦ N, then the negative electrode material layer satisfies: R1>R N 。 2. The negative electrode sheet according to claim 1, characterized in that, The negative electrode material layer also has at least one of the following characteristics: a) When N≧3, R N ≦R i+1 ≦R1, where 2≦i+1≦N-1; b)0<R N ≦3; c) 1≦R1≦6; d)R1 to R N Gradual decrease, gradient decrease, or step decrease are all possible options, with gradient decrease or step decrease being the preferred choice.
3. The negative electrode sheet according to claim 1 or 2, characterized in that, The N satisfies: 2≦N≦8; And / or, the sub-material layer further includes a negative electrode binder, wherein the mass content of the negative electrode binder in the i-th sub-material layer along the direction close to the surface of the current collector is defined as P. i %, then the negative electrode material layer satisfies: P1<P N 。 4. The negative electrode sheet according to claim 3, characterized in that, The negative electrode material layer has at least one of the following characteristics: e) When N ≥ 3, P1 ≦ P i+1 ≦P N Where 2≦i+1≦N-1; f)2≦P N ≦4; g)0<P1≦2.5; h)P1 to P N Gradual increase, gradient increase, or step-like increase are all possible options, with gradient increase being the preferred choice. i) In each of the sub-material layers, the first graphite, the second graphite, and the negative electrode binder are all uniformly distributed; j) The negative electrode binder includes at least one of polyacrylic acid, styrene-butadiene rubber, styrene-acrylic emulsion, and carboxymethyl cellulose.
5. The negative electrode sheet according to claim 3, characterized in that, When N is 2, the negative electrode material layer satisfies: 1≦R1≦4, can be 7 / 3≦R1≦4; and / or, 1.5≦P1≦2.5; and / or, 0<R2≦1, can be 1 / 4≦R2≦3 / 7; and / or, 2≦P2≦3; And / or, when N is 3, the negative electrode material layer satisfies: 7 / 3≦R1≦4, and / or, 1.5≦P1≦2.5, and / or, 3 / 7≦R2≦7 / 3, and / or, 1.8≦P2≦2.8, and / or, 0<R3≦3 / 7, and / or, 2.1≦P3≦3.1; And / or, when N is 4, the negative electrode material layer satisfies: 4≦R1≦6, and / or, 1.5≦P1≦2.1, and / or, 3 / 2≦R2≦4, and / or, 1.7≦P2≦2.3, and / or, 1 / 4≦R3≦3 / 2, and / or, 1.9≦P3≦2.5, and / or, 0<R4≦1 / 4, and / or, 2.2≦P4≦4.
6. The negative electrode sheet according to claim 1, characterized in that, The raw materials for preparing the first graphite include at least one of petroleum low-sulfur coke or needle coke; And / or, the raw materials for preparing the second graphite include at least one of petroleum sulfur coke or needle coke; And / or, the first graphite has at least one of the following characteristics: (1) The particle size of Dv50 is 9-16μm; (2) The particle size of Dv99 is below 65μm; (3) The specific surface area of BET is 0.95-1.45 m² / g; And / or, the second graphite has at least one of the following characteristics: (1) The particle size of Dv50 is 11-18 μm; (2) The particle size of Dv99 is below 80 μm; (3) The specific surface area of BET is 0.8-1.3㎡ / g.
7. The negative electrode sheet according to claim 6, characterized in that, The sulfur content in the low-sulfur petroleum coke is less than 1 wt%. And / or, the sulfur content in the sulfur coke in the petroleum is 1-5 wt%; And / or, the Dv50 particle size of the second graphite is larger than the Dv50 particle size of the first graphite; And / or, the Dv99 particle size of the second graphite is larger than the Dv99 particle size of the first graphite; And / or, the specific surface area of the second graphite is smaller than that of the first graphite.
8. A secondary battery, comprising a positive electrode, a negative electrode, and a separator, characterized in that, The negative electrode is the negative electrode as described in any one of claims 1 to 7.
9. The secondary battery according to claim 8, characterized in that, The positive electrode sheet includes a positive electrode material, the positive electrode material includes a positive electrode lithium supplement, the positive electrode lithium supplement includes at least one of lithium-rich lithium iron ore and lithium-rich lithium nickel ore, and / or the mass content of the positive electrode lithium supplement in the positive electrode material is 0.5-5%.
10. The secondary battery according to claim 9, characterized in that, The cathode material further includes a cathode active material, which includes at least one of lithium iron phosphate and ternary materials, wherein the ternary material includes a ternary cathode material containing nickel, cobalt, and manganese. When the positive electrode active material is lithium iron phosphate, the upper limit voltage of the secondary battery is below 3.8V, and / or, the positive electrode lithium replenishing agent is lithium iron phosphate and lithium nickel phosphate, and the mass ratio of lithium iron phosphate to lithium nickel phosphate is c, 1≤c≤5; and / or, When the positive electrode active material is the ternary material, the upper limit voltage of the secondary battery is 4.2-4.5V, and / or the positive electrode lithium replenishing agent is the lithium iron phosphate and the lithium nickel phosphate, and the mass ratio of the lithium iron phosphate and the lithium nickel phosphate is d, 0 < d ≤ 1.
11. An electrical appliance, characterized in that, Includes the secondary battery as described in any one of claims 8 to 10.
12. The electrical appliance according to claim 11, characterized in that, The electrical equipment includes vehicles.